Timing, risk factors, and causes of foetal and preweaning lamb mortality in lowland production systems involving a range of ewe genotypes - D. Shiels; J.F. Mee; J.P. Hanrahan; C.M. Dwyer; S. Fagan; T.W.J. Keady (Animal, 2025)
Reducing lamb mortality has production, economic and animal welfare benefits. The timing and causes of death and associated risk factors were investigated in a study conducted over 2 consecutive years (involving 1 103 and 1 038 ewes in 2017 and 2018, respectively) in three prolific (average litter size 1.91) indoor-lambing, lowland flocks (in Ireland) that consisted of a range of genotypes, managed in grass-based systems of production. Data were collected from all foetuses and lambs that died (between ∼120 days gestation and weaning at 14 weeks of age); 221 cases in 2017 and 241 cases in 2018. All cases were submitted to a Regional Veterinary Laboratory for necropsy examination using standardised protocols that were developed in advance of case submissions. The majority (60%) of lamb mortality occurred prior to or within 24 h of birth: 46% at or prior to birth and 14% within the first 24 h. Infection (32%) and dystocia (20%) accounted for over half of the mortality. Chlamydia abortus was detected more often in lambs from 2-year-old ewes lambing for the first time than in lambs from older ewes. Dystocia accounted for a statistically significant higher proportion of deaths among purebred lambs born to Texel ewes (49.4%, 95%CI (confidence interval) 36.0 – 62.9) compared to purebred lambs born to Belclare ewes (12.8, 95%CI 2.2 – 23.5). More lambs failed to yield a diagnosis of the cause of death when born to Belclare ewes (29.2%, 95%CI 17.8 – 40.6) than to Suffolk-X ewes (7.4%, 95%CI 0.1 – 14.8). About one−third of lamb mortality cases were adjudged to be preventable through more consideration of management factors during pregnancy, parturition and early postpartum. The use of good hygiene practices at lambing time and optimising lamb birth weight should reduce the level of preweaning lamb mortality in indoor lambing flocks.